Reflections of teaching practice: how postergraduation impacted in pedagogical - Bezerra, Josinaldo Barboza; Sampaio, José Levi Furtado (Geosaberes; Vol 8 No 15 (2017): May - Aug, 2017)
The knowledge stems from the articulation of knowledge that involves the ability to perceive and interpret the everyday reality of society. The essay is the result of a study elaborated from the proposal of the discipline of Stage the Doctoral Course in Geography of the Federal University of Ceará - UFC - in the academic year of 2016. For the accomplishment of the present article an experiment was carried out with the Students of the first semester of Professional Practice in Geography of the UERR. The experiment had as a methodological application of educating with research, involving bibliographical readings, field research, observation in loco, documentary research and the accomplishment of a colloquium to discuss the researched reality. Among the results it is possible to affirm that in learning education research occurs in the process, in which students and teachers interact in a horizontal relationship of coexistence.
Keywords: Educação com Pesquisa; Prática Docente; Ensino Superior.